2022
DOI: 10.1021/acs.orglett.2c01286
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deoxygenative Barbier-Type Reaction

Abstract: An effective deoxygenative C­(sp3)–C­(sp3) bond formation reaction is achieved through electrochemical reduction of alcoholic phosphates or sulfonates with aldehydes or ketones. Alcohol derivatives of phosphates undergo single-electron reduction under electrochemical conditions followed by a spontaneous cleavage of the C–O bond with the exothermic loss of phosphate resulting in an alkyl radical species. Subsequently, radical intermediates are further reduced to carbanions at the cathode, which are in situ trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Hence, in 2022 Tian and Wang's group developed an electrochemical deoxygenation Barbier reaction under simple reaction conditions and high functional group tolerance using the phosphate derivative of alcohols (Scheme 12). 43 The reactions work well for various substituted benzaldehyde allyl aldehydes and aliphatic aldehydes. It is interesting to note that aromatic cyclic ketones and acetophenones are also compatible with this reaction.…”
Section: Electrochemical Deoxidation Of Alcohols With R 3 Pmentioning
confidence: 95%
“…Hence, in 2022 Tian and Wang's group developed an electrochemical deoxygenation Barbier reaction under simple reaction conditions and high functional group tolerance using the phosphate derivative of alcohols (Scheme 12). 43 The reactions work well for various substituted benzaldehyde allyl aldehydes and aliphatic aldehydes. It is interesting to note that aromatic cyclic ketones and acetophenones are also compatible with this reaction.…”
Section: Electrochemical Deoxidation Of Alcohols With R 3 Pmentioning
confidence: 95%
“…[41,[201][202][203] Recently, Tian and Wang and co-workers demonstrated that aliphatic phosphate esters can undergo electrochemical deoxygenative C(sp 3 )À C(sp 3 ) couplings with aldehydes and ketones to furnish alcohol products. [204] Mechanistically, it was proposed that dissociative electron transfer to the phosphate ester furnishes an aliphatic radical that undergoes a second electron transfer to form the carbanion. This species would attack the carbonyl carbon of the coupling partner in a Barbier-like sequence and form the alcohol upon protonation.…”
Section: Methodsmentioning
confidence: 99%
“…The cleavage was postulated to proceed via two initial single‐electron transfers to the phosphate ester to afford a phosphate anion and a carbanion, followed by protonation of the latter to afford the hydrocarbon product [41, 201–203] . Recently, Tian and Wang and co‐workers demonstrated that aliphatic phosphate esters can undergo electrochemical deoxygenative C(sp 3 )−C(sp 3 ) couplings with aldehydes and ketones to furnish alcohol products [204] . Mechanistically, it was proposed that dissociative electron transfer to the phosphate ester furnishes an aliphatic radical that undergoes a second electron transfer to form the carbanion.…”
Section: Electrochemical C−o Bond Activation In Phosphorous‐based Alc...mentioning
confidence: 99%
“…[ 41 , 201 , 202 , 203 ] Recently, Tian and Wang and co‐workers demonstrated that aliphatic phosphate esters can undergo electrochemical deoxygenative C(sp 3 )−C(sp 3 ) couplings with aldehydes and ketones to furnish alcohol products. [204] Mechanistically, it was proposed that dissociative electron transfer to the phosphate ester furnishes an aliphatic radical that undergoes a second electron transfer to form the carbanion. This species would attack the carbonyl carbon of the coupling partner in a Barbier‐like sequence and form the alcohol upon protonation.…”
Section: Electrochemical C−o Bond Activation In Phosphorous‐based Alc...mentioning
confidence: 99%